1993
DOI: 10.1126/science.8503012
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation of Human Smooth Muscle Cells Promoted by Lipoprotein(a)

Abstract: Elevated blood concentrations of lipoprotein(a) [Lp(a)] and its constituent, apolipoprotein(a) [apo(a)], constitute a major risk factor for atherosclerosis, but their physiological activities remain obscure. Lp(a) and purified apo(a) stimulated the growth of human smooth muscle cells in culture. This effect resulted from inhibition of plasminogen activation, and consequently the activation by plasmin of latent transforming growth factor-beta, which is an inhibitor of smooth muscle cell growth. Because smooth m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
182
4
3

Year Published

1993
1993
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(203 citation statements)
references
References 29 publications
9
182
4
3
Order By: Relevance
“…We have recently demonstrated that increased Lp(a) influx from plasma into the arterial intima, as well as decreased efflux of Lp(a) from the intima, results in specific accumulation of undegraded Lp(a) in atherosclerotic lesions. 22 Such excess accumulation of undegraded Lp(a) in atherosclerotic lesions, as also confirmed in the present study, may cause increased proliferation of smooth muscle cells 6 and deposition of fibrin in the intima. 5 Both these effects can potentially accelerate the development of atherosclerotic lesions.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…We have recently demonstrated that increased Lp(a) influx from plasma into the arterial intima, as well as decreased efflux of Lp(a) from the intima, results in specific accumulation of undegraded Lp(a) in atherosclerotic lesions. 22 Such excess accumulation of undegraded Lp(a) in atherosclerotic lesions, as also confirmed in the present study, may cause increased proliferation of smooth muscle cells 6 and deposition of fibrin in the intima. 5 Both these effects can potentially accelerate the development of atherosclerotic lesions.…”
Section: Discussionsupporting
confidence: 66%
“…3 Apo(a) has a high degree of structural similarity to plasminogen, 4 and Lp(a) has been shown to inhibit plasmin formation in vitro. 5 As a result of this effect, Lp(a) inhibits fibrinolysis 5 and accelerates growth of smooth muscle cells 6 in vitro. Although these effects could promote the development of atherothrombotic disease, the significance needs to be determined in vivo.…”
mentioning
confidence: 99%
“…High Lp(a) impairs activation of transforming growth factor-␤ by downregulation of plasmin generation, thereby contributing to smooth muscle cell proliferation. 35 These in vitro findings were confirmed in apo(a) transgenic mouse experiments 36 and found an in vivo equivalent in markedly depressed serum concentration of active transforming growth factor-␤ in advanced human atherosclerosis. 37 Two recent studies demonstrated that Lp(a) induces chemotactic activity to human monocytes in a dosedependent fashion.…”
Section: Kronenberg Et Al Lp(a) Apo(a) Phenotype and Atherogenesissupporting
confidence: 66%
“…[1][2][3] The Lp(a) particle is a normal LDL with apolipoprotein(a) glycoprotein attached to it by a disulfide bond. 1,4 Interestingly, Lp(a) has also been implicated as a stimulus for smooth muscle cell proliferation, 5 and this might provide an additional role for Lp(a) in the pathogenesis of atherosclerosis.…”
mentioning
confidence: 99%